Formalized probability theory and applications using theorem proving - Hasan, Osman, 1975- (Information Science Reference, an imprint of IGI Global, 2015)
"This book discusses some of the limitations inherent in computer systems when applied to problems of probabilistic analysis, and presents a novel solution to these limitations, combining higher-order logic with computer-based theorem proving"--